Effects of intercropping with legume forage on the rhizosphere microbial community structure of tea plants - Jiang, Yuhang; Lin, Xiaoqin; Lin, Wenxiong (Frontiers in Microbiology, 2024)
CONTEXT Intercropping in agriculture is crucial for addressing challenges in intensive tea farming. Forage legumes reduce fertilizer dependence and significantly boost productivity. Currently, intercropping with legumes enhances the environmental conditions of tea plantations and improves tea quality. OBJECTIVE However, the comprehension of the rhizosphere's impact on the associated microbes and the community structure of tea plants is still somewhat constrained. METHODS Hence, four distinct planting methodologies were examined: Monoculture cultivation of Tieguanyin tea plants (MT), Laredo forage soybean (Glycine max Linn.) without partitioning in conjunction with tea (IT), intercropping with tea using plastic partitions (PPIT), and intercropping with tea facilitated by net partitions (NPIT). An absolute quantitative analysis of soil phospholipid fatty acids, labeled with the rhizosphere microbial characteristics of tea plants, was conducted through multi-ion reaction monitoring (MRM). The bacterial and fungal communities were anticipated utilizing the FAPROTAX and FUNG databases, respectively. Gas chromatography was employed to ascertain greenhouse gas emissions across diverse root interaction cultivation systems. RESULTS AND CONCLUSION The rhizospheric influence culminated in a 44.6% increase in total phospholipid fatty acids (PLFAs) and a remarkable 100.9% escalation in the ratio of unsaturated to saturated fatty acids. This rhizospheric enhancement has significantly potentiated the ecological functionalities within the bacterial community, including xylanolysis, ureolysis, nitrogen respiration, nitrogen fixation, nitrite respiration, nitrite ammonification, and nitrate reduction.Mycorrhizomonas, encompassing both ectomycorrhizal and arbuscular forms, has notably colonized the rhizosphere. The interspecific mutualistic interactions within the rhizosphere have resulted in a significant enhancement of plant growth-promoting bacteria, including allorhizobium, bradyrhizobium, rhizobium, burkholderia, gluconacetobacter, and gluconobacter, while concurrently reducing the prevalence of pathogenic microorganisms such as xanthomonas, ralstonia, fusarium, and opportunistic fungi responsible for white and soft rot. The intercropping system showed lower total greenhouse gas emissions than monocultured tea plants, particularly reducing soil CO2 emissions due to complex interspecific rhizosphere interactions. This tea/legume intercropping approach promotes a sustainable ecosystem, enhancing microbial biomass and vitality, which helps suppress rhizospheric pathogens. SIGNIFICANCE These findings are instrumental in enhancing our comprehension of the pivotal practical implications of rhizosphere intercropping, thereby optimizing the structure of rhizosphere communities and alleviating the impact of greenhouse gases within croplands.